O trabalho em saúde nos hospitais de gestão terceirizada: o caso do Estado de Goiás - Vieira, Patrícia Santiago (2013)
In the State of Goiás, the outsourcing management of public hospitals existed for ten years, despite this, studies examining this process are still scarce. The aim of this study was to analyze how outsourcing management influences the work process and the repercussions for the workers. This study consists in the case of two public hospitals in the State of Goiás with outsourced management. The hospitals were selected based on the development of the outsourcing process management. Thus, a hospital has been selected as the process is developed and widely another hospital in which the process is being implemented. For data collection, semi-structured interviews were conducted with ten workers of different occupational categories of each hospital. The choice of the workers was random, and the inclusion criterion that the subject worked directly in health care by the user. The data obtained were categorized on the following categories: productivity / turnover of users, greater job autonomy, control of worker and illness. The Social Organizations (OS) operating in the logic of productivity, it is necessary to maintain a high turnover of users. The policy employed by OSs for management of public hospitals is the logic employed in the private sector and involves the increased job control, reduction of worker‘s autonomy, work intensification and culminate in illness of the workers. It is observed that the centrality of care of hospitals managed by OSs is on productivity and not on meeting the health needs of the user, who often leave the service without having their been met or after receiving an treatment of dubious quality . It is hoped that this research will contribute in analyzes of health work in hospitals outsourced management, increasing the resistance to this form of privatization and the breaking of the right to health.